Research on Literature and Observation of Gui Pi Tang Treating Palpitation - Goh, Pau Kim (2015)
Palpitation refers to a kind of disease where patients felt a conscious heart throb, restlessness, and event not autonomous. Deficiency of heart-spleen cause insufficiency of Qi-blood, which lead to heart lack of nourishment and resulting in palpitation. Gui Pi Tang is created by Yan Yong He according to the theory “Two yang develop from the heart and spleen” stated in <Nei Jing> and Gui Pi Tang is recorded in <Ji Sheng Fang> which indicate excessive thought, heart-spleen fatigue, forgetfulness, and palpitation. In this study, our purpose is to do the further literature study on treating heart-spleen deficiency of palpitation by Gui Pi Tang as well as clinical observation through evaluation using the numerical rate scale (NRS) for the palpitation severity rate and a questionnaire questioning for the condition happening of palpitation and the frequency of palpitation occurred as well as also the tongue manifestation and the pulse condition of subjects before and after the treatment. The total will be five subjects selected for the study, which prior to this treatment. In this study, two of the subjects felt heatiness to the Gui Pi Tang, but they soundly fit with this formula after consuming for one week. Throughout this study, the observational study shows a mean value decrease of 1.7 in total NRS as well as the significantly improved of the palpitation occur condition and times. These results indicate that Gui Pi Tang is a potent formula, which is effective in treating palpitation.